PREVALENSI DAN DISTRIBUSI OSTEOARTRITIS LUTUT BERDASARKAN KARAKTERISTIK SOSIO-DEMOGRAFI DAN FAKTOR RISIKO DI WILAYAH KERJA PUSKESMAS SUSUT I, KECAMATAN SUSUT, KABUPATEN BANGLI PADA TAHUN 2014 - Wan Hasiibi (Intisari Sains Medis, 2015)
An aging process will increase human morbidity caused by degenerative diseases and disability. Based on data in Policlinic of Rheumatology Sanglah Hospital in 2001-2002, Osteoarthritis was the highest case (37%) with proportion of Knee Osteoarthritis was 97%. In Susut I Primary Health Care, which is located in Bangli, Rheumatic placed the second rank from the list of top 10 diseases in 2013.Â This research used cross sectional descriptive method. Sample were elderly who are more than 50 years old and total of sample was 78 which are taken by multistage random sampling method from Banjar Susut Kaja, Susut Village, Susut Subdisctric, Bangli Regency, April 2014.Â The prevalence of Knee Osteoarthritis in elderly who are more than 50 years old in Susut Village in April 2014 was 62,8%. According to socio-demography characteristic , knee osteoarthritis occured more in respondents who are 50-70 years old (61.2%), women (57.1%), and had physical job (farmer, cattleman, labor and army) (65.3%). While, according to risk factors, knee osteoarthritis occured more in respondents who had underweight-normal body mass index (59.2%), with history of workload due to medium-hard (71.4%), with biomechanics factors where respondents who bring goods while worked (71.4%), and the weight of goods estimated more than 25 kg (79.6%), work frequencies with goods more than 4 times a week (53.1%), respondents who had work duration more than 17 years (91.8%), and respondents who had up and down pathway and also using stairs (77.6%). Knee osteoarthritis occured more in respondents without history of knee trauma (87.8%).Â